The Dilemma of Asylum Seekers in Indonesia: Between National Security and Human Security - Miftah Farid Darussalam; Riska Luneto (Universitas Diponegoro, 2025)
This paper aims to examine Indonesia's attitude towards refugees from several countries. This phenomenon is interesting because it is seen from Indonesia's attitude that does not ratify the international immigrant convention, on the other hand Indonesia is trying to fulfill international norms related to human rights. This paper uses the conceptual/theoretical framework of national security and human security. The method used in this paper is a qualitative method with a literature study approach. Indonesia has no obligation to accept immigrants under the international immigrant convention. However, Indonesia chooses to accept immigrants from some countries based on the value of human rights. Thus, Indonesia's prioritization between national security and human security of refugees should prioritize national security if it is threatened by the arrival of immigrants from several countries. The hypothesis in this paper is that the priority level of national security and human security can be determined based on the urgency of the threat to the intended security object. Furthermore, this paper tries to position the state in the implementation of human security.